PENGABDIAN DAN PENGAJARAN PENDIDIKAN ANAK USIA DINI DI TK AL-ARHAM DESA NAGORI SILULUH HUTA 3 - Syakira, Astri (PERNIK, 2024)
This research aims to examine the effectiveness of service and teaching carried out by students at the North Sumatra State Islamic University, Faculty of Tarbiyah and Teacher Training, Early Childhood Education Study Program at Al-Arham Kindergarten, Negori Siluluh Huta 3 Sigogar Village. Community service through early childhood education (PIAUD) is a form of academic assistance in improving the quality of elementary level education. This service and teaching activity aims to increase the competency of kindergarten teachers in implementing learning methods that are creative, innovative and appropriate to the developmental needs of early childhood. The program implemented includes teacher training on a scientific approach, which means the learning process has been designed in such a way that students are more active in learning, then there is also game-based learning, as well as strengthening character education in early childhood. Apart from that, counseling is also provided to parents to support children's development at home. The results of this program show an increase in teachers' knowledge and skills in teaching as well as increased collaboration between the school and parents in supporting children's development. The implications of this activity are expected to be able to create a more effective and enjoyable learning environment for children in kindergarten, as well as supporting their holistic development. This research uses a qualitative method using 3 stages in implementing community service activities, namely 1) Observation, 2) Interviews and 3) Data collection. Keywords : years Devotion, Teaching, Early childhood